2023
DOI: 10.1002/biof.1954
|View full text |Cite
|
Sign up to set email alerts
|

Mapping early serum proteome signatures of liver regeneration in living donor liver transplant cases

Lorena Carmona‐Rodríguez,
Aaron S. Gajadhar,
Irene Blázquez‐García
et al.

Abstract: The liver is the only solid organ capable of regenerating itself to regain 100% of its mass and function after liver injury and/or partial hepatectomy (PH). This exceptional property represents a therapeutic opportunity for severe liver disease patients. However, liver regeneration (LR) might fail due to poorly understood causes. Here, we have investigated the regulation of liver proteome and phosphoproteome at a short time after PH (9 h), to depict a detailed mechanistic background of the early LR phase. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…In the present study we described a general down-regulation of OCM enzymes in PFIC3 livers, which might facilitate cell proliferation for tissue injury repair while the maintenance of MAT2A and B levels support the regulated nature of the process, in contrast to the uncontrolled cell growth that is typically found in cancer development. It is tempting to speculate that the systematic monitoring of OCM would be a useful tool to assess the physiological status of the liver and to allow for discrimination among a controlled regenerative process and tumor progression 45 . It has been also reported that some OCM metabolites might provide alternative therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we described a general down-regulation of OCM enzymes in PFIC3 livers, which might facilitate cell proliferation for tissue injury repair while the maintenance of MAT2A and B levels support the regulated nature of the process, in contrast to the uncontrolled cell growth that is typically found in cancer development. It is tempting to speculate that the systematic monitoring of OCM would be a useful tool to assess the physiological status of the liver and to allow for discrimination among a controlled regenerative process and tumor progression 45 . It has been also reported that some OCM metabolites might provide alternative therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…This multisubunit transmembrane complex is part of the mitochondrial electron transport chain, which drives oxidative phosphorylation. Altered mitochondrial functions have been observed in chronic liver diseases, including alcohol-induced liver disease, nonalcoholic fatty liver disease, viral hepatitis, liver regeneration [28], and primary and secondary cholestasis. Major changes included impairment of the electron transport chain and/or oxidative phosphorylation, leading to decreased oxidative metabolism of various substrates and decreased ATP synthesis [29].…”
Section: Machine Learning Analysismentioning
confidence: 99%